Efficient Synthesis of Cyclopropane‐Fused Heterocycles with Bromoethylsulfonium Salt. Issue 33 (10th July 2013) - Fritz, Sven P.; Matlock, Johnathan V.; McGarrigle, Eoghan M.; Aggarwal, Varinder K.
<x xml:space="preserve">Abstract</x> Lord of the rings! [3.1.0] bicyclic ring systems were synthesized using bromoethylsulfonium triflate and easily available amino acid/aza‐Morita–Baylis–Hillman‐derived allylic amines. The simple transformation displays a very high degree of diastereoselectivity and enables access to a diverse range of densely substituted pyrrolidine‐based bicycles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>